How does smog affect firms' investment behavior? A natural experiment based on a sudden surge in the PM2.5 index - Jingbo Luo (China Journal of Accounting Research, 2017)
This study examines the effect of environmental regulations on the investment behavior of high-polluting enterprises. Our data are from A-share listed firms in China from 2006 to 2014. We use a sudden surge in the PM2.5 index as an exogenous event to conduct a natural experiment. We find that after the event with a series of regulatory policies introduced, investment expenditure declines significantly in local state-owned enterprises (SOEs) and non-state-owned enterprises (non-SOEs), whereas investment opportunity declines significantly in non-SOEs compared with SOEs. However, there are no significant changes in central SOEs' investment expenditure and investment opportunity. Further analysis shows that investment expenditure and investment opportunity decline for high-polluting enterprises located in East China but increase for those located in West China. Our study is the first to investigate the effect of smog on enterprises' investment behavior. Our findings reveal that environmental regulation has influence on the investment behavior of enterprises with different property rights and regional differences.
Keywords: 650; Smog; Investment expenditure; Investment opportunity sensitivity; Environment supervision; Property right